ACUTE EFFECT OF KNEE RIGID THERAPEUTIC TAPE ON AGILITY, SPEED AND MUSCLE POWER IN FEMALE FOOTBALL PLAYERS - Santiniyom, Nonthalee; Intapanya, Theerawith; Chuanboon, Thosapon (Journal of Sports Science and Health, 2023)
Purpose: The purpose of this study was to investigate the effect of knee rigid therapeutic tape on performance in agility, speed, and muscle power among football players. Methods: This research was a cross-over design experimental research. The participants were fifteen female healthy football players, aged between 19-22 years old, and no history of knee injury whom performed two tape conditions on right knee: including non-taping and rigid-taping conditions. Washout period was at least 24 hours between conditions. Agility (FAF’s Slalom), speed (speed 10m, 20m & 40m) and muscle power (vertical jump and standing broad jump) were tested. The mean and standard deviation of the data were calculated and analyzed by a paired t-test with a statistical significance level of 0.05. Results: The results showed that the performance of rigid taping group was slightly higher than the non-taping group in all tests while there were no statistically significant differences between groups in agility, speed, and muscle power (p>0.05). Conclusion: The findings indicated that the knee rigid therapeutic tape did not affect the performance (agility, speed, and muscle power) in female football players.